2013
DOI: 10.1371/journal.pone.0055073
|View full text |Cite
|
Sign up to set email alerts
|

Post-Operative Auto-Transfusion in Total Hip or Knee Arthroplasty: A Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundTotal hip or knee arthroplasty is an elective procedure that is usually accompanied by substantial blood loss, which may lead to acute anemia. As a result, almost half of total joint arthroplasty patients receive allogeneic blood transfusions (ABT). Many studies have shown that post-operative auto-transfusion (PAT) significantly reduces the need for ABT, but other studies have questioned the efficacy of this method.MethodsThe protocol for this trial and supporting CONSORT checklist are available as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
(75 reference statements)
2
28
0
1
Order By: Relevance
“…THA is reported to lead to substantial blood loss, which often leads to blood transfusion [16,17]. Due to the demographic changes that will occur over the next century, an increase in the total number of THAs can be expected; therefore, the total number of blood transfusions will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…THA is reported to lead to substantial blood loss, which often leads to blood transfusion [16,17]. Due to the demographic changes that will occur over the next century, an increase in the total number of THAs can be expected; therefore, the total number of blood transfusions will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, another randomized controlled study on the use of reinfusion systems in THA and TKA found a statistically significant reduction in allogenic blood transfusion when the reinfusion system was used (6%), compared to the control group (19% p=0.015) [17]. In addition, a recent metaanalysis of prospective randomized studies on the use of autologous transfusion systems demonstrated a statistically significant reduction in the need for allogenic blood when the results were pooled [18]. As a result, the authors strongly recommended that autologous reinfusion systems be widely used in primary THA and TKA as a means to reduce the need for allogenic blood transfusions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Kim et al [25] and Holt et al [19] recommended the use of drains as they found a repeated need to change dressings in patients without drains, which resulted in discomfort for the patient and nursing staff even though there was no increase in the infection rate [24]. The use of reinfusion drains with autologous transfusion has shown the benefit of reduction in allogeneic blood transfusion requirement and has been reported to be cost-effective [5,14,25,26]. Various techniques have been tried in order to reduce the potential requirement for allogeneic blood transfusion after joint replacement Our study had its own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Reinfusion drains have gradually outnumbered closed suction drains over the last few years. Some studies have shown that autologous transfusion obtained from reinfusion drains reduces the requirement for homologous blood transfusion [3][4][5], however; some other studies have shown that reinfusion drains do not offer any significant benefit in reducing the transfusion requirements [6,7]. There are conflicting results available regarding the efficacy of routine Preoperative Autologous Donation (PAD) in reducing allergenic blood transfusion; however a recently published study has shown that preoperative autologous donation seems to be effective in reducing allergenic transfusions after total hip arthroplasty but not after total knee arthroplasty [8].…”
Section: Introductionmentioning
confidence: 99%